Cerebral hemisphere dominance and ESP performance in the autoganzfeld. - Alexander, Cheryl H.; Broughton, Richard S. (Journal of Parapsychology, 2001)
The right cerebral hemisphere is often associated with psi abilities, yet there is no substantial evidence to support this claim. Therefore, this study (CL1-Ganzfeld) was designed to examine if a relationship between cerebral hemisphere dominance and ESP performance exists. 50 selected participants were tested for cerebral hemisphere dominance and ESP performance as measured by the Cognitive Laterality Battery (CLB) and the autoganzfeld, respectively. The relationship between ESP scores and personality factors (Myers-Briggs Type Indicator preference scores), geomagnetism, local sidereal time, sender-receiver pairings, and target type was also examined. The selected participants produced a hit rate of 36% (z=1.60, p=.055) in the autoganzfeld. Although this scoring rate falls just short of statistical significance, the effect size (π=.63) is in the upper part of previously predicted ranges. Participants categorized as right-cerebral hemisphere dominant scored fewer direct hits in the autoganzfeld than those categorized as left-cerebral hemisphere dominant, but the difference between the 2 scoring rates is not significant. It is concluded that hemisphere dominance, specifically right-hemisphere dominance as measured by the CLB, is not an important factor associated with psi hitting by selected participants in the autoganzfeld. Reprinted by permission of the publisher.